A Profile of the Assisted Living Direct Care Workforce in the United States. (January 2020) - Kelly, Christopher; Craft Morgan, Jennifer; Kemp, Candace L.; Deichert, Jerome
Background and Objectives: The purpose of this article was to develop a profile of direct care workers (DCWs) in assisted living (AL).Research Design and Methods: We used data from 2014 American Community Survey (ACS) to identify the demographic and employment characteristics of AL DCWs. We collected state training requirements for AL DCWs from the administrative rules of state agencies and interviews with state officials.Results: AL DCWs were more likely than other DCWs to be younger, male, White, English speaking, U.S.-born, never married, and to have attended college. Two Affordable Care Act (ACA)–designated training topics (self-care and the role of the personal care aide) were not required in any state.Discussion and Implications: AL has tapped a unique pool of workers (i.e., younger, male as well as female, and with some college education) but needs to address its workforce needs via training, improvements to overall job quality, and the development of career opportunities.